ANALISIS KASUS PERTUKARAN PULAU RUN MALUKU DAN NIEUW AMSTERDAM MANHATTAN SEBAGAI DASAR PEMIKIRAN TERHADAP TEORI KEDAULATAN NEGARA ATAS SUATU WILAYAH BERDASARKAN PEMANFAATAN SUMBER DAYA ALAM - Alisah, Siti; Collin Adi, Pratama (Jurnal De Jure Muhammadiyah Cirebon, 2023)
The biggest case of exchange that occurred in 1616 was the exchange of Run Island, which is located in the Banda Maluku archipelago, with Nieuw Amsterdam Manhattan Island in North America. Run Island, which at that time was controlled by the British through the colonial invasion of nations from Europe to nations in Asia, Europe and America, when Run Island was controlled by the British, was not yet controlled by the Dutch, where the Dutch had set foot on the archipelago as colonizers. which has controlled the island of Banda as the largest spice producer in the archipelago. Feeling that the position of the Dutch was threatened by the arrival of the British on the island of Run, the British entered into an agreement with the tribal chiefs on the island of Run as an official statement of surrender, as well as a commitment from the spice traders on the island of Run to sell their spice products to the British trade committee. England decided to seize Nieuw Amsterdam in 1664. During 1665-1667, England and the Netherlands fought for control of the seas and trade routes in the West Indies and East Indies, exchanging the islands of Run and Nieuw Amsterdam through the Treaty of Breda in 1667. In their negotiations, the Dutch were the winners of the war. asked England to allow Run and Suriname to be annexed by the Netherlands, while in exchange Nieuw Amsterdam would remain in British hands. The reason for exchanging the islands of Run and Nieuw Amsterdam was because the Dutch wanted spices in the form of nutmeg. Nutmeg is a spice commodity that in the past was only found on Banda Island, including Run Island. In the context of the Napoleonic war, England attacked the Banda Islands in 1810. In contrast to when the Dutch left Nieuw Amsterdam in 1674 without serious damage, England left the Banda Islands with heavy damage. own nutmeg production in the colonies. This competition also destroyed nutmeg production in the Banda Islands and the Dutch monopoly. Keywords: Sovereignty, Territorial, Natural Resources